O que ainda não sabemos e precisávamos de saber para o ensino de Português Língua Não Materna - Martins, Cristina; Silva, Fátima; Pinto, Jorge (Revista da Associação Portuguesa de Linguística, 2022)
This paper aims at identifying gaps in the current understanding of the acquisition of Portuguese as a non-native language that research should fill in order to meet the needs of teachers of Portuguese as a non-native language. We draw attention to the need for research on the followingtopics: profiling of learners and how variables relevant to these profiles intersect with interlinguistic knowledge and development; description of sequencing patterns of language structures in learners’ interlinguistic development (built-in syllabus); description of learners’ prior linguistic knowledge, presenting as multilingual competence, and how this competence interacts with metalinguistic awareness and the interlinguistic development of learners; review of available pedagogical models and consideration of how different approaches can selectively respond to the development of specific linguistic competences. In advancing our understanding of these issues and overcoming the gaps we have identified, we call for a reconnection between research on non-native language acquisition and the most effective approaches to its teaching, reclaiming a focus on what is taught and what can/should be taught, rather than merely how it is taught. Finally, we propose the creation of teacher training opportunities with a greater regard for the multilingual competences of learners and teachers themselves.